2023
DOI: 10.3390/cancers15041221
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Extracellular Matrix Regulates the Response of Osteosarcoma 3D Spheroids to Doxorubicin

Abstract: The extracellular matrix (ECM) modulates cell behavior, shape, and viability as well as mechanical properties. In recent years, ECM disregulation and aberrant remodeling has gained considerable attention in cancer targeting and prevention since it may stimulate tumorigenesis and metastasis. Here, we developed an in vitro model that aims at mimicking the in vivo tumor microenvironment by recapitulating the interactions between osteosarcoma (OS) cells and ECM with respect to cancer progression. We long-term cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…B cells are vital to adaptive immunity and significantly impact the OS TME by producing antibodies, presenting antigens, and secreting cytokines. Most of the literature suggests that B cells promote tumor progression; however, recent investigations have demonstrated the close association of B cells with the prognosis of OS patients and the response to immunotherapy [15,18]. Recently, Petitprez et al reported that B cells were the most decisive prognostic factor in improved survival and a high response rate to PD1 blockade in a phase 2 clinical trial of soft-tissue sarcoma [60,61].…”
Section: B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…B cells are vital to adaptive immunity and significantly impact the OS TME by producing antibodies, presenting antigens, and secreting cytokines. Most of the literature suggests that B cells promote tumor progression; however, recent investigations have demonstrated the close association of B cells with the prognosis of OS patients and the response to immunotherapy [15,18]. Recently, Petitprez et al reported that B cells were the most decisive prognostic factor in improved survival and a high response rate to PD1 blockade in a phase 2 clinical trial of soft-tissue sarcoma [60,61].…”
Section: B Cellsmentioning
confidence: 99%
“…In addition to the cellular components, noncellular elements of the TME, such as the ECM and extracellular vesicles (EVs), also contribute to OS progression and metastasis. The ECM, a three-dimensional network of proteins and polysaccharides, provides a scaffold for tumor cells, influences their behavior through biomechanical and biochemical cues, and is crucial for modeling and studying drug response [14,15]. By comparison, EVs, tiny membrane-bound particles released by cells into the extracellular matrix, serve as vehicles for intercellular communication, carrying a cargo of proteins, lipids, and nucleic acids that can alter the phenotype of recipient cells.…”
Section: Introductionmentioning
confidence: 99%
“…This 3D environment was found to maintain the stem cell phenotype for a longer duration compared to conventional two-dimensional (2D) cultures, thereby enhancing the relevance of screening, and improving targeting efficiency during pharmaceutical testing [ 44 ]. Additionally, Cortini et al developed 3D OS spheroids that mimic not just the oncogenesis and cellular proliferation processes, but also the complex cell ECM interactions [ 60 ]. These 3D OS spheroids, composed of metastatic or non-metastatic OS cells and mesenchymal stromal cells (MSCs), displayed ECM protein deposition (including Type I collagen, Type III collagen, and fibronectin) at the interface between tumor cells and MSCs [ 60 ].…”
Section: Advance In Os Cells and Modelsmentioning
confidence: 99%
“…Additionally, Cortini et al developed 3D OS spheroids that mimic not just the oncogenesis and cellular proliferation processes, but also the complex cell ECM interactions [ 60 ]. These 3D OS spheroids, composed of metastatic or non-metastatic OS cells and mesenchymal stromal cells (MSCs), displayed ECM protein deposition (including Type I collagen, Type III collagen, and fibronectin) at the interface between tumor cells and MSCs [ 60 ]. Their research underscored that ECM protein deposition plays a crucial role in evaluating drug response, suggesting that targeting these proteins could potentially improve outcomes in chemoresistant tumors [ 60 ].…”
Section: Advance In Os Cells and Modelsmentioning
confidence: 99%
“…In certain cases, the cells of interest can bind with polymeric biomaterials to form a matrix in which cells create a microenvironment that highly mimics the original tumor. Spheroids have been used to study the roles of tumor cells and the microenvironment through the incorporation of varying types of cells, such as mesenchymal stem cells and osteosarcoma cells [77]. The most notable advantages of this model are its low production costs and high reproducibility.…”
Section: Mfs Spheroids and Sarcospheresmentioning
confidence: 99%